1980
DOI: 10.3177/jnsv.26.271
|View full text |Cite
|
Sign up to set email alerts
|

A possible role of Z protein in dietary control of hepatic triacylglycerol synthesis.

Abstract: SummaryThe effects of fasting and refeeding on hepatic Z protein were investigated in rats. When [U-14C]palmityl-CoA was added to the liver cytosol fraction from fat-free refed rats, more binding of labeled palmityl-CoA to the Z-protein region was found than in the case of fasted rats. Also the radioactivities in specific precipitations of the palmityl-CoA binding protein with anti-Z immunoglobulin G were higher in the refed rats. The Z protein which stimulated diacylglycerol acyltransferase may be involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The decrease in the desaturase specific activity was directly related with the decrease in concentration of the myristic acid−FABP complex. Previous studies reported that hepatic fatty acid binding protein (hFABP) may specifically direct the utilization of fatty acids toward either esterification ( , ) or oxidative paths (). Albumin was an ineffective replacer of hFABP in stimulating the activity of some microsomal enzymes utilizing fatty acids ( , ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in the desaturase specific activity was directly related with the decrease in concentration of the myristic acid−FABP complex. Previous studies reported that hepatic fatty acid binding protein (hFABP) may specifically direct the utilization of fatty acids toward either esterification ( , ) or oxidative paths (). Albumin was an ineffective replacer of hFABP in stimulating the activity of some microsomal enzymes utilizing fatty acids ( , ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that hepatic fatty acid binding protein (hFABP) may specifically direct the utilization of fatty acids toward either esterification ( , ) or oxidative paths (). Albumin was an ineffective replacer of hFABP in stimulating the activity of some microsomal enzymes utilizing fatty acids ( , ). This suggested the role of FABP in providing fatty acids to their enzymes may be more than a substrate solubilizer.…”
Section: Resultsmentioning
confidence: 99%
“…acylCoA :glycerol-3-phosphate acyltransferase [116][117][118], diacylglycerol acyltransferase [119,120], lysophosphatidic acid acyltransferase [121] and acyl-CoA :cholesterol acyltransferase [122,123]. Rat liver FABP appears to have both stimulatory and inhibitory effects on both mitochondrial and microsomal acylCoA synthetases [117,[124][125][126].…”
Section: A New Look At Fabps In Acyl-coa Metabolismmentioning
confidence: 99%
“…FABPs have been shown to enhance the activity of several microsomal acyl-CoA utilizing enzymes involved in cholesterolester-, phospholipid-and triacylglycerol synthesis, i.e. acyl-CoA:glycerol-3-phosphate acyltransferase (Jolly et al, 1997;Haq et al, 1987;Burnett et al, 1979;Mishkin and Turcotte, 1974b) diacylglycerol acyltransferase (Iritani et al, 1980;O'Doherty and Kuksis, 1975) lysophosphatidic acid acyltransferase (Bordewick et al, 1985), and acyl-CoA: cholesterol acyltransferase (Scallen et al, 1985;Grinstead et al, 1983). Rat liver FABP appears to have both stimulatory and inhibitory effects on both mitochondrial and microsomal acyl-CoA synthetases (Noy et al, 1986;Burnett et al, 1979;Ockner and Manning, 1976;Wu-Rideout et al, 1976).…”
Section: Fatty Acid Binding Protein and Sterol Carrier Protein-2 In Acyl-coa Metabolismmentioning
confidence: 99%